Nanoprecipitate‐Strengthened High‐Entropy Alloys - Liyuan Liu; Yang Zhang; Jihong Han; Xiyu Wang; Wenqing Jiang; Chain‐Tsuan Liu; Zhongwu Zhang; Peter K. Liaw (Advanced Science, 2021)
Abstract Multicomponent high‐entropy alloys (HEAs) can be tuned to a simple phase with some unique alloy characteristics. HEAs with body‐centered‐cubic (BCC) or hexagonal‐close‐packed (HCP) structures are proven to possess high strength and hardness but low ductility. The faced‐centered‐cubic (FCC) HEAs present considerable ductility, excellent corrosion and radiation resistance. However, their strengths are relatively low. Therefore, the strategy of strengthening the ductile FCC matrix phase is usually adopted to design HEAs with excellent performance. Among various strengthening methods, precipitation strengthening plays a dazzling role since the characteristics of multiple principal elements and slow diffusion effect of elements in HEAs provide a chance to form fine and stable nanoscale precipitates, pushing the strengths of the alloys to new high levels. This paper summarizes and review the recent progress in nanoprecipitate‐strengthened HEAs and their strengthening mechanisms. The alloy‐design strategies and control of the nanoscale precipitates in HEAs are highlighted. The future works on the related aspects are outlined.